Plasma NGAL and glomerular filtration rate in cardiac transplant recipients treated with standard or reduced calcineurin inhibitor levels. (February 2014) - Gustafsson, Finn; Gude, Einar; Sigurdardottir, Vilborg; Aukrust, Pål; Solbu, Dag; Goetze, Jens-Peter; Gullestad, Lars
Aim : Predictors of renal recovery following conversion from calcineurin inhibitor- to proliferation signal inhibitor-based therapy are lacking. We hypothesized that plasma NGAL (P-NGAL) could predict improvement in glomerular filtration rate (GFR) after conversion to everolimus.Patients & methods : P-NGAL was measured in 88 cardiac transplantation patients (median 5 years post-transplant) with renal dysfunction randomized to continuation of conventional calcineurin inhibitor-based immunosuppression or switching to an everolimus-based regimen.Results : P-NGAL correlated with measured GFR (mGFR) at baseline (R 2 = 0.21; p < 0.001). Randomization to everolimus improved mGFR after 1 year (median [25–75 % percentiles]: ΔmGFR 5.5 [-0.5–11.5] vs -1 [-7–4] ml/min/1.73 m 2 ; p = 0.006). Baseline P-NGAL predicted mGFR after 1 year (R 2 = 0.18; p < 0.001), but this association disappeared after controlling for baseline mGFR.Conclusion : P-NGAL and GFR correlate with renal dysfunction in long-term heart transplantation recipients. P-NGAL did not predict improvement of renal function after conversion to everolimus-based immunosuppression.